Revivir el interés en las aulas (Bridging Cultures, 2019)
Nowadays, it is increasingly common to hear teachers remark the students’ lack of interest in their classrooms. Without searching a diagnosis to such phenomenon but acknowledging that all of us teachers are faced with the task of motivating students in our classes at some point in our careers, this paper purports to present some tools provided by various foreign language teaching methods which may be useful for this porpuse. Since the surge of audiolingualism in the 50s up to the latest methods, such as the communicative method, different authors have claimed they had found the “magic” solution to achieve outstanding teaching results. A more realistic procedure in our classrooms is using different strategies depending on the context and the teachers’ needs, which is consistent with a “post method” theory.
Keywords: English as a foreign Language; Teaching Methods; Students’ Motivation; Teaching Practice; Engaging Students